1991
DOI: 10.1093/nar/19.11.3035
|View full text |Cite
|
Sign up to set email alerts
|

Steady state kinetics and inhibition of HIV-1 reverse transcriptase by a non-nucleoside dipyridodiazepinone, BI-RG-587, using a heteropolymeric template

Abstract: Steady state kinetics and inhibition by a dipyridodiazepinone of the reverse transcriptase from human immunodeficiency virus type 1 (HIV) were studied using a heteropolymeric RNA template with a sequence from the authentic initiation site on the HIV genome. For addition of the first deoxynucleotide to primer, kcat/KM is 0.05 (nM-min)-1 and KM is 10 nM. When all 4 deoxynucleotide triphosphates are present and processive synthesis occurs, catalysis is less efficient; kcat/KM = .0077 (nM-min)-1 and KM = 100 nM fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…As observed by Reardon and Miller (1990) and Kopp et at. (1991) the overall efficiency of catalysis, KcatlK m , differed little between homo-and heteropolymeric template-primers (Table 1 and 2). PFA has earlier been reported (Goldman et el., 1991) to displace from HIV-1 RTa compound, L-697,639 and to be mutually exclusive with L-696,229 (Goldman et sl., 1992), both compounds being very similar to L-697,661.…”
Section: Vrang Et El Personal Communication) the Two Mutantsupporting
confidence: 77%
“…As observed by Reardon and Miller (1990) and Kopp et at. (1991) the overall efficiency of catalysis, KcatlK m , differed little between homo-and heteropolymeric template-primers (Table 1 and 2). PFA has earlier been reported (Goldman et el., 1991) to displace from HIV-1 RTa compound, L-697,639 and to be mutually exclusive with L-696,229 (Goldman et sl., 1992), both compounds being very similar to L-697,661.…”
Section: Vrang Et El Personal Communication) the Two Mutantsupporting
confidence: 77%
“…Inhibitors of HIV-1 RT fall into two categories: the nucleoside and the nonnucleoside reverse transcriptase inhibitors (NNRTIs). The nucleoside RT inhibitors are substrate analogs that act as chain terminators, whereas the NNRTIs are a chemically diverse group of compounds that noncompetitively inhibit DNA polymerization (1)(2)(3).…”
mentioning
confidence: 99%
“…I), all of the drugs are highly specific for HIV-I; i.e., they do not inhibit a variety of other DNA polymerases including HIV-RT type 2. Although most of the drugs (such as nevirapine and the TlBO derivatives) appear to be mechanistically noncompetitive for primer, template, and nucleotide (Kopp et al, 1991;Romero et al, 1991), at least one inhibitor (HEPT) has been reported to be competitive with respect to the natural substrate dTTP (Baba et al, 1991). In addition, nonnucleoside inhibitors show a lower cellular toxicity than nucleoside inhibitors (Pauwels et al, 1990; Romero et al, 1991).…”
mentioning
confidence: 99%